2017
DOI: 10.5606/ehc.2017.52891
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to avoid intra-articular screw penetration with minimal use of fluoroscopy in the application of distal radius volar plate?

Abstract: ÖZAmaç: Bu çalışmada distal radius volar plak uygulamasında minimum floroskopi kullanılarak eklem içi vida penetrasyonundan kaçınmanın ve böylece cerrahi ekibin radyasyona maruz kalma riskinin minimuma indirilmesinin mümkün olup olmadığı araştırıldı. Hastalar ve yöntemler: Haziran 2014 -Mayıs 2016 tarihleri arasında instabil distal radius kırığı olan 50 hastada (22 erkek, 28 kadın; ort. yaş 43.52 yıl; dağılım 18-76 yıl) kırık redüksiyonunu takiben distal vida ile volar plak uygulaması minimum floroskopi kullan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Factors contributing to screw penetration into the joint include a mismatch in the shape of the distal radius and plate design, the misperception of the shape of the lunate fossa, and inadequate reduction. 16 The use of intraoperative techniques to confirm screw penetration into the joint, such as imaging by slightly elevating the forearm in the anteroposterior and lateral views to depict the joint plane on fluoroscopy and the use of 3D reconstructed images, are recommended. 16 Soong et al reported that radiographic images from multiple directions are needed to accurately evaluate the placement of all screws in VLP fixation of the distal radius.…”
Section: Discussionmentioning
confidence: 99%
“…Factors contributing to screw penetration into the joint include a mismatch in the shape of the distal radius and plate design, the misperception of the shape of the lunate fossa, and inadequate reduction. 16 The use of intraoperative techniques to confirm screw penetration into the joint, such as imaging by slightly elevating the forearm in the anteroposterior and lateral views to depict the joint plane on fluoroscopy and the use of 3D reconstructed images, are recommended. 16 Soong et al reported that radiographic images from multiple directions are needed to accurately evaluate the placement of all screws in VLP fixation of the distal radius.…”
Section: Discussionmentioning
confidence: 99%
“…The volar locking plate system was established in 2000 and has rapidly become gold standard in treatment of distal radius fractures [ 7 10 ]. It is a safe procedure, offering biomechanically stable fixation and allowing early rehabilitation [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The former derives from insufficient fracture reduction [ 12 , 13 ] and intraarticular positioned screws [ 8 , 14 ], the latter from plate misplacement (especially ruptures of the flexor pollicis longus tendon) [ 15 , 16 ] or dorsally protruding screws (especially ruptures of the extensor pollicis longus tendon) [ 8 , 14 , 17 ]. To correct these mistakes intraoperatively and avoid postoperative CT and revision surgery, the surgeon needs competent knowledge of the complex distal radius anatomy [ 7 , 18 ] and high-quality imaging [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] The main goals of treatment are maintaining normal anatomy and obtaining a functional joint. [4] The most complicated fractures of the distal radius are highenergy, comminuted, intraarticular, and unstable fractures.…”
mentioning
confidence: 99%